Effect of TiC addition on the mechanical behaviour of Al2O3–SiC whiskers composites obtained by SPS. Issue 8 (July 2016) - Gutiérrez-González, C.F.; Suarez, M.; Pozhidaev, S.; Rivera, S.; Peretyagin, P.; Solís, W.; Díaz, L.A.; Fernandez, A.; Torrecillas, R.
Abstract: Large Al2 O3 –SiCw and Al2 O3 –SiCw –TiC composites disks (150 mm diameter) were prepared in this work by using the spark plasma sintering technique. The main physical and mechanical properties of these composites were measured in different disk zones in order to test out the homogeneity of the sintering process. It has been found that the incorporation of TiC as reinforcing phase to the Al2 O3 –SiCw composite, improved densification, mechanical strength and hardness. This result was analyzed in terms of SEM microstructure observations showing that the presence of TiC inhibited the alumina grain growth.